Study on Failure Analysis of Parallel Shaft Gear of Wind Turbine Gearbox - Zhao Dengli; Yang Kuoling; Dong Ying (Jixie chuandong)
Aiming at the problem of the failure of the downwind side gear teeth on the high-speed intermediate gear shaft of wind turbine gearbox，the fishbone analysis method is used to analyze the reasons of design，manufacture，material，assembly and operation maintenance. Based on the experimental research and simulation analysis method，it is determined that the failure of the gearbox is due to the lack of downwind direction in the assembly process of the gearbox. The control of bearing compression leads to the excessive clearance of bearings，which results in the eccentric load of axle gears.